Religious involvement and the forgiving personality - Etienne Mullet (2003)
The relationship between religious involvement and forgiveness was assessed in three samples of Western Europeans living in a social environment dominated by the Catholic tradition. The samples comprised nonbelievers/nonattendees, believers/nonattendees, believers/regular attendees, and religious people. Age and religious involvement were shown to affect the willingness to forgive in an interactive way: The effect of religious involvement was stronger for the elderly group. We also found that what made the difference in the willingness to forgive was mainly the social commitment to religion (attendance in church and the taking of vows), not mere personal beliefs. In addition, age and religious involvement were found to affect blockage towards forgiveness in an additive way.